Kinetics of Ru(III) Catalysed Oxidation of Cyclohexanol by Bromamine-T in Hydrochloric Acid - Singh, J.P.N.; Kumar Singh, Rajiv (Asian Journal of Chemistry, 2010)
The kinetics of Ru(III) catalysed oxidation of cyclohexanol by acidic solution of bromamine-T (BAT) have been reported. The reaction shows first-order kinetics in each of bromamine-T, cyclohexanol, H+ ions and Ru(III). Decreasing effect of chloride ions was observed. Ionic strength variation did not influence the reaction rate. Negligible effect of addition of p-toluene sulphonamide (one of the reaction products) was observed. A suitable mechanism consistent with observed kinetic results has been proposed.